Given: "y=3x-1+Ce^{-3x}" ... (1)
Find the differential equation for the given family of curves by eliminating the arbitrary constant "C" .
Differing the given equation (1) with respect to "x" , we get
"\\frac{dy}{dx}=3(1)-0+Ce^{-3x}(-3)=3-3Ce^{-3x}"
That is "\\frac{dy}{dx}=3-3Ce^{-3x} ... (2)"
Eliminate "C" from the equations (1) and (2).
From equation (2), "3Ce^{-3x} =3-\\frac{dy}{dx} \\Rightarrow C=e^{3x}-\\frac{1}{3}e^{3x}\\frac{dy}{dx}"
Substitute "C" in equation (1), we get "y=3x-1+\\left ( e^{3x}-\\frac{1}{3}e^{3x}\\frac{dy}{dx} \\right )e^{-3x}=3x-1+1-\\frac{1}{3}\\frac{dy}{dx}"
"\\Rightarrow y=3x-\\frac{1}{3}\\frac{dy}{dx}"
Replace "\\frac{dy}{dx}" by "-\\frac{dx}{dy}" to get the differential equation of the orthogonal trajectories.
Then, we get
"y=3x-\\frac{1}{3}\\left ( -\\frac{dx}{dy} \\right )=3x+\\frac{1}{3}\\frac{dx}{dy}"
"\\frac{dx}{dy}+9x=3y"
The above is a first order linear differential equation of the form "\\frac{dx}{dy}+p(y)x=g(y)" ,
where "p(y)=9" and "g(y)=3y"
General solution to the linear differential equation is
"x(" Integrating Factor) = "\\int (" Integrating Factor)("g(y))dy+c" ,
where Integrating Factor = "e^{\\int p(y)dy}"
Using the above, Integrating Factor = "e^{9y}"
General solution is "x(e^{9y})=\\int (e^{9y})(3y)dy+c"
Use integration by parts to evaluate the right side integral.
Then, we get
"x=\\frac{y}{3}-\\frac{1}{27}+ce^{-9y}"
Therefore, orthogonal trajectories for the given family of curves is
"x=\\frac{y}{3}-\\frac{1}{27}+ce^{-9y}" , where "c" is arbitrary constant.
Comments
Leave a comment